All the flowers kneeling - Tran, Paul, (Poet) (Penguin poets., 2022)
"A profound meditation on physical, emotional, and psychological transformation in the aftermath of imperial violence and interpersonal abuse, from a poet both "tender and unflinching" (Khadijah Queen)"--